Tantangan dan Strategi Implementasi Manajemen Pendidikan dalam Meningkatkan Kualitas Pembelajaran di Era Digital di SDN 067245 Medan - Anggita Uli Angel Gultom; Desi Sri Kelengna Surbakti; Nadhilah Nazwa; Dini Syarafina; Rizki Fadilah (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
Based on the results of observations at SDN 067245 Medan, education is something related to the development of a person's potential in three areas, namely how to view life, attitude to life, and life skills. The success of an education is not always determined by teaching materials, learning materials, infrastructure or other tools but is also determined by management and the organization that manages it. To improve the implementation of education, education must be linked to information and communication technology, and must be creative and innovative in implementing education management, so that education can become an advantage in the midst of world civilization. The digital era is when everyone has access to various information via the network. The aim of education management itself is to plan fair, quality, efficient and responsible education and increase positive perceptions about education. The type of research used by researchers is Qualitative Research. Where the data collection instruments used are in the form of observation sheets, questionnaires, interviews and field notes